ASSESSMENT THE RESPONSE OF SAGITTARIO ITALIAN WHEAT VARIETY FOR DIFFERENT CONCENTRATIONS OF ORGANIC FERTILIZERS IN MANY SPRAYING DATES - Aliyas, IbraheemM.; Hassen, Salem A.; Neamah, Hasan Mohsen (International Journal of Research -GRANTHAALAYAH, 2017)
Considers Bio-fertilizer eco-friendly, characterize by their high importance in improve the chemical, physical and biological traits of soil was better from chemical fertilizer Where the latter causes negative effects on biosphere. The study was conducted to assessment the response of Wheat of Sajittario variety (W. S .V) for two concentration levels of FitoAlg organic fertilizer(F.A.O.F) in three spraying dates and their effects on the vegetative growth and yield properties by using the randomized complete block design (RCBD) with three replications .The research was conducted in Mosul city within the province of Nineveh / Iraq at the agrarian season 2014 to study the response of (W. S .V) for two concentrations of (F.A.O.F) were (a1) 2 ml/L and (a2)4ml/L in three spraying dates (b1) 23/2, (b2) 2/3 and (b3) 9/3 ,which sprayed in tillering stage on vegetative growth , for studying their effects on the following properties; plant height cm, tillers number/plant , dry biological weight ( ton/ h), seeds number/ spike ,weight of 1000 seeds gm , straw weight (ton/ h) and total yield (ton/ h). By using the randomized complete block design (RCBD) with three replications. Results showed that variance analysis of the concentration of (F.A.O.F) with spraying dates were have significant effect at 0.05 probability level in the following characteristics; tiller number, weight of 1000 seed and yield ,also have significant effect at 0.01 probability level only in spike seeds number ,others properties were non-significant at both 0.05, 0.01 levels as table (2). Showed the first spraying date significant effect at 0.05 probability level their superior from others in weight 1000 seed and spike seeds number where was same effected with two others in dates of spraying as in table(3). Showed both concentrations the same effect in all of the traits at 0.05 levels. Where the first concentration had high value than both others concentrations as in table (4). The interaction effect between spraying dates and concentrations of (F A O F) on vegetative growth and yield characters for (W. S .V), where all vegetative and yield properties where the yield reached 4.86(to/ h). That indicates, to response the variety to (F. A O. F) by suitable concentration 2ml/l and fit the date of spraying 23/02 (a1b1) as in table (5), addition for good dominant environmental conditions in the study region, as well as the good genetic traits in the variety.